VIRTUAL EMOTION CONTROL OF HUMAN BEINGS: BENEFITS AND ADVERSE EFFECTS - Khambaji Godawale, Shivaji; Chandrakant Deshmukh, Prashant; Sugaraj Jadhavrao, Swapnil; Bhiku Pisal, Mahadeo (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The concept of virtual emotion control, encompassing technologies and methods that influence human emotions through digital means, has gained significant attention in recent years. This review paper explores the benefits and adverse effects associated with virtual emotion control. Benefits include therapeutic applications in mental health and enhanced user experiences in digital environments. However, the adverse effects, such as privacy concerns, ethical dilemmas, and potential psychological impacts, necessitate a balanced perspective. This paper synthesizes current research to provide an overview of the dual-edged nature of virtual emotion control, highlighting areas for future investigation.